2012
DOI: 10.1172/jci61319
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 increases anxiety by reducing GABAA receptor agonist methylglyoxal

Abstract: Glyoxalase 1 (Glo1) expression has previously been associated with anxiety in mice; however, its role in anxiety is controversial, and the underlying mechanism is unknown. Here, we demonstrate that GLO1 increases anxiety by reducing levels of methylglyoxal (MG), a GABA A receptor agonist. Mice overexpressing Glo1 on a Tg bacterial artificial chromosome displayed increased anxiety-like behavior and reduced brain MG concentrations. Treatment with low doses of MG reduced anxiety-like behavior, while higher doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
216
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(228 citation statements)
references
References 65 publications
12
216
0
Order By: Relevance
“…However, several contradictory reports have also been published. To further explore the mechanism of anxiety regulation, Hambsch et al (2010) and Distler et al (2012) reported that methylglyoxal (MG), the substrate for GLO1, is responsible for the regulation of anxiety. The neuroendocrine, neurochemical, and neurogenetic profiles of the CHF and CLF lines have not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, several contradictory reports have also been published. To further explore the mechanism of anxiety regulation, Hambsch et al (2010) and Distler et al (2012) reported that methylglyoxal (MG), the substrate for GLO1, is responsible for the regulation of anxiety. The neuroendocrine, neurochemical, and neurogenetic profiles of the CHF and CLF lines have not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The broad spatial and temporal expression patterns highlight the crucial importance of the glyoxalase system for biological function. Recent studies revealed alterations in GLO1 expression in neuropsychiatric disorders for mood (Fujimoto et al, 2008), anxiety (Distler et al, 2012;Hovatta et al, 2005;Kromer et al, 2005;Politi et al, 2006) and schizophrenia (Itokawa et al, 2014), but their expression levels have not been examined in postmortem brains. Our analysis, however, did not observe any differences in expression levels of both genes between schizophrenia and controls in BA46 and the hippocampal CA1 subfield.…”
Section: Discussionmentioning
confidence: 99%
“…In attempts to link Glo1 metabolically to dysfunctional brain metabolism, MG concentration in brain tissue of mice has been estimated at approximately 170-360 μM [27] and 5 μM MG [28], which appear to be overestimates compared with those of 0.3 and 1.5 μM brain stem/midbrain and cortex when peroxidase and other interferences in the MG assay are blocked [29]. MG was found to agonize the GABA A (γ -aminobutyric acid A) receptor in primary cerebellar granule neurons with a median effective concentration EC 50 of 10.5 μM.…”
Section: Anxiety Phenotypementioning
confidence: 99%
“…MG was found to agonize the GABA A (γ -aminobutyric acid A) receptor in primary cerebellar granule neurons with a median effective concentration EC 50 of 10.5 μM. MG agonism at the GABA A receptor was proposed as a mediator of sedation to explain increased Glo1 CNV with an anxiety phenotype [28]. MG concentration in mouse brain tissue is approximately 7-fold lower than this [29] and only approached the EC 50 value with dosing of 300 mg of MG/kg of body mass [28], similar to doses that have previously produced acute toxicity [30].…”
Section: Anxiety Phenotypementioning
confidence: 99%
See 1 more Smart Citation